Foreign studies - Endō, Shūsaku 1923-1996; Williams, Mark (Linden Press, 1990)
Three young Japanese have varying experiences while living in Europe.
Keywords: Endo, Shusaku <1923-1996> -- Translations into English; Japanese fiction